Effect of Underlap and its Soft Error Performance in 30 nm Junctionless-based 6T-SRAM Cell - Chitra Pandy; Ramakrishnan Narayanan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
As CMOS device is scaling down significantly, the sensitivity of Integrated Circuits (ICs) to Single Event Upset (SEU) radiation increases. The Sensitivity of ICs to  soft errors emerge as reliability threat which motivates  significant interest in the development of various techniques both at the device and circuit level for SEU hardness in SRAM memories. To facilitate the scaling the concept of underlap Gate-Source/Drain (G-S/D) was suggested in the literature. Lun is one of the sensitive geometrical parameter considered to differ from 1 nm to 5 nm in a SEU radiating environment. The effect of Gate-Source/Drain underlap (Lun) on soft error performance in 30 nm Junctionless Transistor (JLT) based on 6T-SRAM cell has been examined through extensive mixed mode-device and circuit simulations using TCAD. The critical dose observed in JLT based 6T-SRAM with Lun ranging from 1 nm to 5 nm to flip the cell is given by Linear Energy Transfer (LET) between 0.05 to 0.06 pC/µm. The simulation result analyzes electrical and SEU radiation parameters to study its impact on JLT based 6T-SRAM cell.